Potency of hyaluronic acid from eggshell-membrane for open gingival embrasure reconstruction following orthodontic tooth movement (a histomorphological study) - Suparwitri, Sri; Alhasyimi, Ananto Ali (2022)
Background: The aim of this research was to assess the effectiveness of eggshell-membrane (ESM)-containing hyaluronic acid (HA) in the treatment of open gingival embrasure (OGE) following orthodontic tooth movement (OTM).